Geoökologische Gebirgsforschung als angewandte Umweltforschung:: Ein Bericht zur Entwicklung und zu den Zukunftsaufgaben der IGU-Commission Mountain Geoecology and Sustainable Development - Stadelbauer, Jörg (ERDKUNDE, 1992)
The IGU Commission Mountain Geoecology and Sustainable Development is part of an international and interdisciplinary network of institutes and organizations contributing to the study of mountain areas. During the last two decades, the main approach of mountain geoecology shifted from physiogeographic and biological topics to applied environmental ones. The UNCED held at Rio de Janeiro in 1992 accepted the Mountain Agenda as apart of the Agenda 21 dealing with the prospects of environmental and socio-economic development beyond our century. Those agenda define the conceptual framework of further studies in mountain regions. The organizational basis is a close network embracing the International Mountain Society, the IGU Commission, specialized institutes and NGO's as well. The IGU Commission meeting at Davis, CA, in 1992 discussed this network of international mountain research and the tasks of further investigations. The symposium forming part of a continuous series of conferences also gave a lot of examples for recent applied research. An excursion to the Sierra Nevada and the White Mountains confronted the participants with the intense research work which is done by the Department of Geography of the University of California at Davis.